ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DALAM PERENCANAAN PRODUKSI PADA PT. OLYMPIC FURNITURE GEMILANG BOGOR - Erika Yunira; Gatot Wahyu Nugroho (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to determine the control of raw material inventory in production planning at PT. Olympic Furniture Gemilang. The main raw materials used by PT. Olympic Furniture Gemilang is a wood particle board (PB), medium density fiberboard (MDF) and solid wood. PT. Olympic Furniture Gemilang processes wood into wardrobes, tables, kitchen sets and other versatile shelves. The problems faced by the company in relation to the inventory of raw materials include optimal purchasing, security inventory, reordering and the total cost of raw material inventory. The results show that the amount of economical raw materials for each purchase of raw materials for PB in 2021 is 315.84 m3 with a purchase frequency of 19 times, Safety Stock is 349.636 m3, Reorder Point is 1.909.192 m3, and TIC according to the EOQ method is Rp. 45.234,653. MDF raw materials in 2021 are 137.61 m3 with a purchase frequency of 10 times, Safety Stock is 44,233 m3, Reorder Point is 416,785 m3 and TIC according to the EOQ method is Rp 19.708,875. The raw material for Soid Wood in 2021 is 103.45 with a purchase frequency of 8 times, Safety Stock is 85.849 m3, Reorder Point is 296.425 m3 and TIC according to the EOQ method is Rp. 14.817,424.